2010
DOI: 10.1097/eja.0b013e32833d91c3
|View full text |Cite
|
Sign up to set email alerts
|

Improved analgesia after the realisation of a pain management programme in ICU patients after cardiac surgery

Abstract: The intervention programme successfully reduced the occurrence of unacceptable pain. Further improvement of pain management should focus on the prevention of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 19 publications
0
38
1
Order By: Relevance
“…While the data sets of pain levels in the first postoperative week of both the ICU and ward were available as a result of a previous study [11], the telephone interviews were performed specifically for this study. Patients were asked to describe their symptoms for the 2 preceding weeks retrospectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the data sets of pain levels in the first postoperative week of both the ICU and ward were available as a result of a previous study [11], the telephone interviews were performed specifically for this study. Patients were asked to describe their symptoms for the 2 preceding weeks retrospectively.…”
Section: Discussionmentioning
confidence: 99%
“…Pain scores were recorded both in the ICU and on the ward from day 0 until day 7 after surgery. Following local clinical practice, pain levels were scored at least 3 times a day while in the ICU [11], and at least once a day while on the ward. Upon arrival in the ICU, patients received a continuous intravenous infusion of morphine (2 mg h À1 ) in combination with acetaminophen (1 g orally or rectally 4 times a day), according to standard protocol [11].…”
Section: Peri-and Postoperative Procedures and Pain Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain management program with specific guidelines also have a role in managing postoperative pain effectively. Jocelyn et al in their practice guideline used paracetamol and In-domethacin (NSAID) on regular basis along with intermittent doses of intravenous morphine and found that it was 95% effective in relieving pain [26].…”
Section: Discussionmentioning
confidence: 99%
“…Between 63% and 77% of patients report experiencing pain while in the ICU. 1 An observational study in 128 Italian ICUs of 661 postoperative patients found that 36.3% of patients did not receive any analgesia in the first 48 hours of their ICU stay. 2 "Pain control" was the reason for the opioid administration in only 54.5% of instances in which an opioid was given.…”
Section: Prevalence Of Pain In the Intensive Care Unitmentioning
confidence: 99%